International partnerships for a just energy transition: Findings from South Africa - Heiner von Lüpke; Charlotte Aebischer; Martha Bola\~nos (DIW Weekly Report, 2023)
In 2021, the G7 and South Africa agreed upon the Just Energy Transition Partnership (JETP). This new instrument in interna- tional cooperation should support emerging and developing economies in a just energy transition and in phasing out coal. It is intended to facilitate equal partnerships between donors and recipients, thereby also facilitating the energy transition. An evaluation of the South African JETP shows that while it is de facto an international policy process for setting the course for the energy transition, it still lacks the necessary legitimacy and institutional framework. It can also be seen that the cur- rent finance instruments, which usually tie transfer payments to conditions, are only partially effective; they often lack the necessary flexibility in the policy process. In contrast, a joint agreement between donors and recipients that is based on shared policy goals, norms, and reciprocity can facilitate both the necessary cooperation and the subsequent just energy transition. Intensifying political dialogues, conducting mutual policy peer reviews, and improving both the regulatory frame- work and the legitimacy of cooperation can be useful tools for an effective partnership.
Keywords: O13; O19; Q54; H87; 330; Just energy transition partnerships; international climate finance; development assistance; South Africa